Knjižničarji in knjige o matematičnih vedah v knjižnici ljubljanskega jezuitskega kolegija - Južnič, Stanislav (Knjižnica, 2005)
For the very first time in Slovenian historiography, we describe the life and work of the first Carniolian librarians at the Jesuit college library of Ljubljana. We researched the last catalogue of the Ljubljana Jesuit library issued in 1775. Unfortunately, the fire destroyed a good part of the library a year before cataloguing. We proved that some of the books with Jesuit exlibris in contemporary National and University Library of Ljubljana were not catalogued in 1775. We pay special attention on the rarely known facts considering the still recognizable book numbers on the covers of the books written during cataloguing in 1775. We claimed that the mathematical books were very important part of the Ljubljana Jesuit library.
Keywords: Licejska knjižnica; Ljubljana; jezuiti; knjižnično gradivo; matematika; mathematics; zgodovinski pregledi